2017
DOI: 10.18632/oncotarget.14717
|View full text |Cite
|
Sign up to set email alerts
|

MTDH promotes glioma invasion through regulating miR-130b-ceRNAs

Abstract: Cell invasion is crucial for high mortality and recurrence rate in glioma. Epithelial-mesenchymal transition (EMT) is an important step in cancer invasion. Metadherin (MTDH) contributes to EMT in several cancers, but the role and mechanism of MTDH in EMT-like process of glioma remain unknown. Here we demonstrate that MTDH was overexpressed in glioma tissues and cells and induced EMT-like change and invasion of glioma cells. Interestingly, MTDH could modulate the expression of a group of glioma-related miRNAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…High MTDH expression is also identified as an independent prognostic indicator of the survival of patients with gliomas (40). Previous studies demonstrated that MTDH is involved in the initiation and progression of glioma through the regulation of cell proliferation, colony formation, metastasis, EMT in vitro and decreased tumour growth in vivo (20)(21)(22). Therefore, these findings suggested that MTDH could represent a possible target for the therapy of patients with this deadly disease.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…High MTDH expression is also identified as an independent prognostic indicator of the survival of patients with gliomas (40). Previous studies demonstrated that MTDH is involved in the initiation and progression of glioma through the regulation of cell proliferation, colony formation, metastasis, EMT in vitro and decreased tumour growth in vivo (20)(21)(22). Therefore, these findings suggested that MTDH could represent a possible target for the therapy of patients with this deadly disease.…”
Section: Discussionmentioning
confidence: 94%
“…To delineate the molecular mechanisms by which miR-379 inhibits glioma cell proliferation and invasion, we identified the targets of miR-379 in glioma. Bioinformatics analysis indicated that MTDH, which has been reported to contribute to the initiation and formation of glioma (20)(21)(22), was predicted as a candidate target of miR-379 ( Fig. 3A).…”
Section: Mtdh Is a Direct Target Of Mir-379 In Glioma Cellsmentioning
confidence: 99%
“…The shown to facilitate the translocation of NF-κB into the nucleus and interacts with the p65 subunit of NF-κB which acts as a coactivator for NF-κB to modulate gene expression of targeted genes. 45,55 Moreover, IκB kinase β-mediated MTDH phosphorylation is critical for IκB-α degradation as well as NF-kB-dependent gene expression and cell proliferation, which correlates with survival in cancer patients. 56 Thus, to summarize, our study demonstrated that serum levels of CCL18 may serve as potential biomarker for diagnosis of SCCHN, and CCL18 plays an important role during invasion, metastasis and EMT of SCCHN.…”
Section: Nf-κb Activation Is Involved In Ccl18/mtdhmediated Metastamentioning
confidence: 99%
“…21 Some studies reported that MTDH plays an oncogene role in different cancers and promotes cancer growth and metastasis. [22][23][24] MDTH is involved in multiple biological processes of cancer, including cell migration and invasion, differentiation, cell survival and apoptosis, metastasis and even chemotherapy resistant. 25 On the basis of the above evidence, this gene may serve as a practicable target for improving therapies for cancers.…”
Section: Introductionmentioning
confidence: 99%